Social Anxiety dan Perceived Performance terhadap User Acceptance dan Kepuasan Pengguna dalam Penggunaan Ticket-Vending Machine - Kartika Aprilia Benhardy (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
Purpose – This research aims to evaluate the relevance of providing ticket-vending machines at railway stations in the context of train ticket purchases by measuring user satisfaction based on factors that influence user acceptance of the machine.Methodology – The research is quantitative and uses a descriptive approach. Non-probability sampling with a purposive sampling technique was used to select a sample of 230 respondents who have used the ticket-vending machine service. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software.Findings – The study's results indicate that social anxiety and perceived performance have a positive and significant effect on user acceptance, with the same result for the relationship between user acceptance and user satisfaction. Originality/Novelty – This research contributes to the decision of rail service providers in Indonesia to maintain the provision of ticket-vending machines for purchasing tickets at train stations considering that the ticket purchase options that have been provided are easier and more sophisticated at this time by using 4 (four) variables where each relationship in the research model were analyzed using PLS-SEM.Implications – The provision of ticket-vending machines is still very relevant for KAI and MRT passengers in Indonesia because they are considered to meet expectations and are reliable even when used independently. Therefore, KAI and MRT service providers are expected to maintain quality assurance.